Two Widely Spaced Initiator Binding Sites Create an HMG1-Dependent Parvovirus Rolling-Hairpin Replication Origin - Cotmore, Susan F. (American Society for Microbiology, 2000)
Minute virus of mice (MVM) replicates via a linearized form of rolling-circle replication in which the viral nickase, NS1, initiates DNA synthesis by introducing a site-specific nick into either of two distinct origin sequences. In vitro nicking and replication assays with substrates that had deletions or mutations were used to explore the sequences and structural elements essential for activity of one of these origins, located in the right-end (5′) viral telomere. This structure contains 248 nucleotides, most-favorably arranged as a simple hairpin with six unpaired bases. However, a pair of opposing NS1 binding sites, located near its outboard end, create a 33-bp palindrome that could potentially assume an alternate cruciform configuration and hence directly bind HMG1, the essential cofactor for this origin. The palindromic nature of this sequence, and thus its ability to fold into a cruciform, was dispensable for origin function, as was the NS1 binding site occupying the inboard arm of the palindrome. In contrast, the NS1 site in the outboard arm was essential for initiation, even though positioned 120 bp from the nick site. The specific sequence of the nick site and an additional NS1 binding site which directly orients NS1 over the initiation site were also essential and delimited the inboard border of the minimal right-end origin. DNase I and hydroxyl radical footprints defined sequences protected by NS1 and suggest that HMG1 allows the NS1 molecules positioned at each end of the origin to interact, creating a distortion characteristic of a double helical loop.